Graphene oxide/epoxy acrylate nanocomposite production via SLA and importance of graphene oxide surface modification for mechanical properties - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2021)
Purpose Traditional nanocomposite production methods such as in situ polymerization, melt blending and solvent technique, have some deficits. Some of these are non-homogeneous particle distribution, setup difficulties, time-consuming and costly. On the other hand, three-dimensional printing technology is a quite popular method. Especially, Stereolithography (SLA) printing offers some benefits such as fast printing, easy setup and smooth surface specialties. Furthermore, surface modification of Graphene Oxide (GO) and its effects on polymer nanocomposites are quite important. The purpose of this study is to examine the effect of surface modification of GO nanoparticles on the mechanical properties and morphology of epoxy acrylate (BisGMA/1,6 hexane diol diacrylate) matrix nanocomposites. Design/methodology/approach In this study, Ultraviolet (UV) curable end groups of synthesized resin were linked to functional groups of graphene oxide, which are synthesized by the Tour method, which is a kind of modified Hummer method. In addition, synthesized GO nanoparticle's surfaces were modified by 3-(methacryloyloxy) propyl trimethoxysilane. Significant weight percentages of GO were added into the epoxy acrylate resin. Different Wt.% of modified graphene oxide/acrylate resins was used to print test specimens with SLA type three-dimensional printer. Findings Surface modification has a significant effect on tensile strength for graphene oxide nanoparticles contained composites. In addition, a specific trend was not observed for tensile test results of non-modified graphene oxide. The tendency of impact and hardness test finding were similar for both surfaces modified and non-modified nanoparticles. Finally, the distribution of particles was homogeneous. Originality/value This paper is unique because of the inclusion of both surface modifications of graphene oxide nanoparticles and SLA production of nanocomposites with its own production of three-dimensional printer and photocurable polymer resin.
Keywords: Surface modification; SLA; Graphene nanocomposite; Tour method; UV curable GO